Perirenal Fat Thickness: A Surrogate Marker for Metabolic Syndrome in Chinese Newly Diagnosed Type 2 Diabetes - Guo, Xiu Li; Tu, Mei; Chen, Yang; Wang, Wei (Frontiers in Endocrinology, 2022)
Objective Increasing evidence suggested that perirenal fat thickness (PrFT) was associated with metabolic risk factors. This study aimed to assess the association between PrFT and metabolic syndrome (MetS) in Chinese newly diagnosed type 2 diabetes (T2DM), further evaluating the ability of PrFT in identifying MetS. Method A total of 445 Chinese newly diagnosed T2DM were enrolled in this study from January to June 2021. Demographic and anthropometric information were collected. PrFT was evaluated by CT scan on Revolution VCT 256. MetS was based on the Chinese Diabetes Society definition. Receiver operating characteristic (ROC) curve was conducted to assess the optimal cutoff value of PrFT in identifying MetS. Results Overall, the prevalence of MetS was 57.5% (95% CI: 54.0–64.0%) in men and 58.9% (95% CI: 52.3–65.5%) in women separately. The correlation analysis showed that PrFT was significantly correlated with metabolic risk factors like body mass index, waist circumference, triglycerides, high-density lipoprotein cholesterol, systolic blood pressure, diastolic blood pressure, uric acid, and insulin resistance. PrFT was also shown to be independently associated with MetS after adjustment for other confounders. The odds ratios (ORs, 95% CI) were 1.15 (1.03–1.38) in men and 1.31 (1.08–1.96) in women (P < 0.05). The ROC curves showed a good predictive value of PrFT for MetS. The areas under the curve of PrFT identifying MetS were 0.895 (95% CI: 0.852–0.939) in men and 0.910 (95% CI: 0.876–0.953) in women (P < 0.001). The optimal cutoff values of PrFT were 14.6 mm (sensitivity: 83.8%, specificity: 89.6%) for men and 13.1 mm (sensitivity: 87.6%, specificity: 91.1%) for women. Conclusions PrFT was significantly associated with MetS and showed a powerful predictive value for it, which suggested that PrFT can be an applicable surrogate marker for MetS in Chinese newly diagnosed T2DM. Clinical Trial Registration This study was registered in clinicaltrials.gov (ChiCTR2100052032).